Low-dose and standard-dose whole-body [18F]FDG-PET/CT imaging: implications for healthy controls and lung cancer patients - Ferrara, Daria; Shiyam Sundar, Lalith Kumar; Chalampalakis, Zacharias; Geist, Barbara Katharina; Gompelmann, Daniela; Gutschmayer, Sebastian; Hacker, Marcus; Kertész, Hunor; Kluge, Kilian; Idzko, Marco; Langsteger, Werner; Yu, Josef; et al. (Frontiers in Physics, 2024)
Aim. High-sensitivity PET imaging with advanced whole-body (WB) or total-body PET/CT systems permits reducing injected tracer activity while preserving diagnostic quality. Such approaches are promising for healthy control studies or for exploring inter-organ communication in systemic diseases. This study assessed test/retest variations in key organs FDG-uptake from low-dose (LD) and standard-dose (STD) [18F]FDG-PET/CT imaging protocols in healthy controls and lung cancer patients.Methods. 19 healthy controls (19-62 y, 46-104 kg, 10M/9F) and 7 lung cancer patients (47-77 y, 50-88 kg, 4M/3F) underwent [18F]FDG-PET/CT imaging. All subjects were injected first ("test", LD) with 28±2 MBq, and underwent a dynamic (0-67 min post-injection) WB imaging protocol with LD-CT. 90 min post-LD injection, subjects were repositioned and injected with 275±16 MBq ("retest", STD). A second LD-CT and STD-CT was acquired for healthy controls and patients, respectively. Static images (55-67 min post-injection) were considered for subsequent analysis. CT images were used to automatically segment target volumes-of-interest.Standardized-uptake-values normalized to body weight (SUVBW) were extracted for each volume-of-interest. Mean SUVBW were compared for both LD/STD conditions with paired t-tests. In patients, FDG-avid lesions were manually delineated on LD and STD static images.Effective dose levels were estimated from both the CTs and PET acquisitions.Organ-based mean SUVBW were similar between LD and STD (mean %-difference ≤5%) in both healthy controls and cancer patients, except in the heart. Intra-control test/retest variability was significant in brain, heart and skeletal-muscle (p<0.05). While 17 lesions were delineated on STD images of the patients, only 10/17 lesions were identified on LD images due to increased image noise. Lesion-based mean SUVBW were similar between LD/STD acquisitions (p=0.49, %-difference =10%). In patients, the effective doses were: (1.9±0.2) mSv (LD-CT), (16.6±5.4) mSv (STD-CT), (0.5±0.1) mSv (LD-PET) and (4.6±0.3) mSv (STD-PET).FDG injections in healthy controls and lung cancer patients yielded comparable mean SUVBW, except in the heart. Dose levels may be reduced for [18F]FDG-PET imaging without a loss in mean SUVBW accuracy, promoting LD-PET/CT protocols for studying multi-organ metabolic patterns. In oncology patients, this approach may be hindered by lower diagnostic quality in the presence of significant noise.